Expressão das proteínas envolvidas no trânsito de cálcio miocárdico de ratos obesos por dieta hiperlipídica saturada - Deus, Adriana Fernandes de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Obesity is a current problem that occurs in developed and developing countries, in different age groups and social classes. It is considered a chronic metabolic disease characterized by excessive fat accumulation in relation to lean tissue, is associated with increased mortality risk, reduced life expectancy and numerous comorbidities as type II diabetes mellitus, insulin resistance, dyslipidemia and cardiovascular diseases. Several molecular, structural, hemodynamic and functional modifications of the heart in humans and animals have been frequently associated with obesity. Although the increase in adipose tissue may cause changes in cardiac performance, the mechanisms responsible for these changes are unclear. Different factors have been suggested as responsible for possible cardiac functional abnormalities in obesity models, including the regulatory proteins of myocardial calcium handling. It is well established in the literature the association of saturated fatty acids and increased risk of cardiovascular diseases such as coronary artery disease. Some authors observed changes as apoptosis and cardiac hypertrophy. Researchers found in obese Wistar rats by high fat diet, 70% unsaturated fatty acids and 30% saturated, that the increase in the nuclear area and volume myocyte were correlated significantly with saturated fatty acids, although the levels were lower than unsaturated. The literature states that obesity by fat unsaturated diet does not promote changes in the expression of proteins related to myocardial calcium handling; however, there are no studies that evaluated this relationship in obesity models induced by saturated high-fat diet. The aim of this study was to test the hypothesis that obesity by saturated high-fat diet leads to changes in the expression and / or phosphorylation of proteins related to myocardial calcium handling. Wistar rats were divided into two groups: control (C, n=18; saturated normolipidic diet) and ...

A obesidade é um problema atual que ocorre em países desenvolvidos e subdesenvolvidos, em diferentes faixas etárias e classes sociais. Considerada uma doença metabólica crônica, caracterizada pelo acumulo excessivo de gordura em relação à massa magra tecidual, está associada com o aumento de risco de mortalidade, redução na expectativa de vida e numerosas comorbidades como, diabetes mellitus tipo II, resistência à insulina, dislipidemia e doenças cardiovasculares. Diversas modificações, moleculares, estruturais, hemodinâmicas e funcionais, do coração, em humanos e animais, têm sido frequentemente associadas com a obesidade. Embora a elevação do tecido adiposo possa provocar mudanças no desempenho cardíaco, os mecanismos responsáveis por estas alterações não estão esclarecidos. Diferentes fatores têm sido sugeridos como responsáveis pelas possíveis anormalidades funcionais cardíacas em modelos de obesidade, entre eles, as proteínas reguladoras do trânsito de cálcio miocárdico. É bem difundida na literatura a associação de ácidos graxos saturados e aumento do risco de doenças cardiovasculares como, doença arterial coronariana. Alguns autores observaram alterações como, apoptose e hipertrofia cardíaca. Pesquisadores verificaram em ratos Wistar obesos por dieta hiperlipídica, 70% de ácidos graxos insaturados e 30% de saturados, que o aumento na área e volume nuclear do miócito se correlacionou significantemente com os ácidos graxos saturados, embora os seus níveis fossem menores que os insaturados. Na literatura consta que a obesidade por dieta hiperlipídica insaturada não promove alteração na expressão das proteínas relacionadas ao trânsito de cálcio miocárdico; entretanto, não há estudos que avaliaram esta relação na obesidade induzida por dieta hiperlipídica saturada. O objetivo desse estudo foi testar a hipótese que a obesidade por dieta hiperlipídica saturada acarreta...
Keywords: Miocardio; Coração - Doenças; Obesidade - Fisiopatologia; Calcio; Ratos Wistar; Heart - Diseases; Calcium